The effectiveness of flash cards as a tool for educating elementary school students on the prevention of dengue hemorrhagic fever (DHF) - Fahrul Rusdianto; Fajrina Hidayati; Helmi Suryani Nasution; Oka Lesmana (Indonesian Public Health-Observer Information Forum (IPHORR) Kerjasama dengan Persatuan Perawat Nasional Indonesia (PPNI), 2026)
Background: Dengue Hemorrhagic Fever (DHF) remains a public health problem in Indonesia, including Jambi City. Low levels of knowledge and preventive attitudes toward DHF among school-age children may increase the risk of disease transmission. Flash card media was selected as an educational medium because it is visual, attractive, and suitable for elementary school students’ learning characteristics. Purpose: to determine the effectiveness of flash card media as DHF prevention education for elementary school students. Method: a quasi-experimental design with a pretest-posttest control group approach. The research was conducted at SD Negeri 31 Jambi City as the intervention group and SD Negeri 02 Jambi City as the control group. The sample consisted of 68 respondents, including 34 students in the intervention group and 34 students in the control group. Data were collected using questionnaires on DHF prevention knowledge and attitudes. Data analysis was performed using paired t-test and Wilcoxon test with a 95% confidence level. Results: The results showed that the mean knowledge score in the intervention group increased from 9.82 to 12.12 with a p-value of 0.000 (p<0.05). The mean attitude score in the intervention group also increased from 29.35 to 30.91 with a p-value of 0.004 (p<0.05). Meanwhile, the control group showed no significant improvement in students’ knowledge and attitudes. Conclusion: flash card media is effective in improving knowledge and attitudes toward Dengue Hemorrhagic Fever (DHF) prevention among elementary school students in Jambi City. Flash card media can be used as an alternative health promotion medium that is attractive and easy for school-age children to understand.